Geografia eleitoral: análise espacial dos votos dos deputados estaduais de Goiás nas eleições de 2006 e 2010 - Pereira, Bruno Magnum (2014)
The Electoral Geography emerges in France for over one hundred years, with the geographer André Siegfried. However, geography has neglected this area for decades Political Geography. Recently the interest in studies of elections comes back to geographical science, emerging analysis suggests that the spatial dimension as a possible explanatory variable. Thus, considering the importance of the role of space in the analysis of elections as we have assumed that the vote is a given space. Therefore, we propose a spatial analysis of the votes of election in 2006 and 2010 for state representative of Goiás. Thus, the overall goal was to analyse how place shapes the distribution of votes in the space and their relationship to the political representation of the state legislators Goiás. To this end, we seek through rates effective number of candidates, the concentration index / dispersion and dominance index spatialize the votes in Goiás, with the unit of analysis the municipality, understanding that this is the place of politics. Spatial voting patterns were related to the production of parliamentary deputies had checked for electoral connection in Goiás. As a result, we identified from the index effective candidates that concentrate the votes in a few candidates. At the same time, the majority of elected State Representative vote is concentrated within five municipalities, namely, in a few municipalities receive a number of votes that effectively contributes to his election. The axis of dominance shares the most votes with other candidates. Thus, the most common pattern among State Representative is concentrated of Goiás-shared. By relating to parliamentary production in the Legislative Assembly of Goiás, it was found that, somehow, the spatial patterns of voting is related to the more particularistic action, which grants benefits or interests located in more universalist parliamentary actions. This led us to consider that the appreciation of the spatial dimension contributes greatly to the analysis of politics and elections.